Optional Immunizations as Parameter of Parent’s Behavioral Change in Health Needs of Their Off-springs - Abdul Azis A.; Aliamran Rasjid; Sudijanto Sudijanto; Rachmat Kurdi (Paediatrica Indonesiana, 1979)
Services provided by Utan Kayu M.C.H. Clinic, Medical School, University of Indonesia, were introduced to the surrounding community through individual as well as through group contacts. It is desirable to measure the degree of health education efforts of the clinic especially of parents behavioral change in health needs of their children. For the purpose of the study a stratified systematic record sampling of the active-files of patient in 1975 were undertaken.